(untitled) (UNWE Yearbook, 2020)
The Western Balkans plays an important role in the international Islamist terrorist organizations’ structure. The region is becoming an important strategic junction of international terrorism and has been witnessing an active proliferation of the imported militant Pan-Islamist ideology aiming at gradual creation of the so called “Balkan Caliphate”. Starting from 2012, the Western Balkan countries have been making serious efforts to counter these threats and with the active participation of the international community they have stared adopting and implementing new relevant national strategies and legislation.